HPLC Profiling with At‐line Microdilution Assay for the Early Identification of Anti‐fungal Compounds in Plants from French Polynesia. Issue 2 (23rd September 2013) - Bertrand, Samuel; Petit, Charlotte; Marcourt, Laurence; Ho, Raimana; Gindro, Katia; Monod, Michel; Wolfender, Jean‐Luc
ABSTRACT Introduction The search for anti‐fungal compounds has maintained a scientific interest notably due to existing difficulties in the treatment of mycoses and their increasing occurrence in hospitals. Objective Development of a simple method to rapidly identify anti‐fungal compounds in crude plant extracts based on a HPLC microfractionation approach combined with an at‐line anti‐Candida assay. Methods The scale of the semi‐preparative HPLC microfractionation was adapted to fit the sensitivity of the Candida albicans anti‐fungal in a 96‐well microdilution assay. This format is also compatible for MS and NMR dereplication of the active compounds. Results Based on the screening of 12 crude extracts of plants from French Polynesia, three plants, which displayed various levels of anti‐fungal activities, were selected to assess the efficiency of the HPLC anti‐fungal profiling and the scale necessary for microfractionation. The same anti‐Candida assay was performed on the HPLC microfractions collected using a generic profiling method. Analysis of active microfractions by MS and NMR issued from the most active extract enabled an efficient dereplication of the compounds responsible for the anti‐fungal activity. Conclusion A generic HPLC anti‐fungal profiling method was developed which revealed that only 50 mg of crude extract were sufficient for a rapid identification of compound(s) responsible for the anti‐Candida activity. This approach was illustrated by the study of Alphitonia zizyphoides, a plant traditionally used to treat dermatomycoses. Copyright © 2013 John Wiley & Sons, Ltd.